2018
DOI: 10.3390/soilsystems2030044
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and Mobility of Mercury in Soils Contaminated by Legacy Emissions from a Chemical Factory in the Rhône Valley in Canton of Valais, Switzerland

Abstract: Legacy contamination of soils and sediments with mercury (Hg) can pose serious threats to the environment and to human health. Assessing risks and possible remediation strategies must consider the chemical forms of Hg, as different Hg species exhibit vastly different environmental behaviors and toxicities. Here, we present a study on Hg speciation and potential mobility in sediments from a chemical factory site, and soils from nearby settlement areas in the canton of Valais, Switzerland. Total Hg ranged from 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…The content of methyl-Hg relative to THG was 1.9% in the roots of rice under background conditions and 0.55% in the leaves; in areas of Hg mining sites, the concentrations were 0.07% in the roots and 0.01% in the leaves; and in areas with artisanal Hg mining sites, the concentrations were 0.63% in the roots and 0.02% in the leaves [98]. Methyl-Hg in heavily contaminated soil in the Rhône Valley (Switzerland) accounted for < 0.8% of THg [99]. A number of factors that control microbial activity and/or the geochemical speciation of inorganic Hg 2+ govern MeHg formation in the environment [100].…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of methyl-Hg relative to THG was 1.9% in the roots of rice under background conditions and 0.55% in the leaves; in areas of Hg mining sites, the concentrations were 0.07% in the roots and 0.01% in the leaves; and in areas with artisanal Hg mining sites, the concentrations were 0.63% in the roots and 0.02% in the leaves [98]. Methyl-Hg in heavily contaminated soil in the Rhône Valley (Switzerland) accounted for < 0.8% of THg [99]. A number of factors that control microbial activity and/or the geochemical speciation of inorganic Hg 2+ govern MeHg formation in the environment [100].…”
Section: Referencesmentioning
confidence: 99%
“…Moreover, the natural/background Hg level was 0.08 mg/ kg in Brazil [121], 0.05 mg/kg in India [122], 0.23 mg/kg in New Zealand [123], 0.11 mg/kg in the Norwegian Arctic [124] and 0.4 mg/kg in Paris [125]. Most soil Hg was found as soil matrix-bound divalent Hg (Hg II ), whereas elemental Hg (Hg 0 ) was undetectable in soils [85,99]. Table 7 presents examples of the concentrations of Hg in the soils in the vicinity of industrial emission sources according to different authors, The highest Hg contents were found in soils near Hg mines: Almaden in Spain, with 2000 years of mining and ore processing (< 8889 mg kg −1 ) [126]; Idrija in Slovenia, with 500 years of mining activity (< 2759 mg kg −1 ) [97,127]; and in Alaska (5326 mg kg −1 ) [125].…”
Section: Mercury In Soilmentioning
confidence: 99%
“…Two experiments were performed in 5-L polypropylene pots (19 cm in diameter) with perforated lids, where soil and earthworms were incubated. For both experiments, soils were collected (in October 2015 for experiment 1 and October 2016 for experiment 2) in a field near the town of Raron in Canton Valais, Switzerland (46 • 18 10.6" N, 7 • 48 34.2" E), where long-term severe Hg pollution had been reported [24,[26][27][28]. The pollution originated from sediments of a canal that received a large amount of Hg (estimated at 50 to 250 tons) from ca.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The content of methyl-Hg relative to THG was 1.9% in the roots of rice under background conditions and 0.55% in the leaves; in areas of Hg mining sites, the concentrations were 0.07% in the roots and 0.01% in the leaves; and in areas with artisanal Hg mining sites, the concentrations were 0.63% in the roots and 0.02% in the leaves [107]. Methyl-Hg in heavily contaminated soil in the Rhône Valley (Switzerland) accounted for < 0.8% of THg [108].…”
Section: Methylmercurymentioning
confidence: 99%